b - Luthy, Christoph Herbert (Amsterdam : Amsterdam University Press, 2012)
"When David Gorlaeus (1591-1612) passed away at 21 years of age, he left behind two highly innovative manuscripts. Once they were published , his work had a remarkable impact on the evolution of seventeenth-cent ury thought. However, as his identity was unknown, divergent interpreta tions of their meaning quickly sprang up. Seventeenth-century readers u nderstood him as an anti-Aristotelian thinker and as a precursor of Des cartes. Twentieth-century historians depicted him as an atomist, natura l scientist and even as a chemist. And yet, when Gorlaeus died, he was a beginning student in theology. His thought must in fact be placed at the intersection between philosophy, the nascent natural sciences, and theology. The aim of this book is to shed light on Gorlaeus' family cir cumstances, his education at Franeker and Leiden, and on the virulent A rminian crisis which provided the context within which his work was wri tten. It also attempts to define Gorlaeus' place in the history of Dutc h philosophy and to assess the influence that it exercised in the evolu tion of philosophy and science, and notably in early Cartesian circles. "---P. [4] of cover.
Includes bibliographical references (pages 195-215) and index.
Also published online through the online OAPEN library.
Keywords: Gorlaeus, David, -- 1591-1612.; Philosophers -- Netherlands; Atomism; Physics -- History; Philosophy -- History; Religion and science